Cinética de sinterização para sistemas à base de SnO2 por taxa de aquecimento constante - Tebcheran, S. M. [UNESP] (2003)
Dense tin oxide based ceramics are very promising for technological applications such as varistors and crucibles for melting very corrosive glasses. Several additives have been used in small concentrations as densifying aids for this oxide. In the present study the sintering kinetics of tin oxide was studied considering the effect of sintering atmosphere and of the MnO2 concentration. SnO2-MnO2 systems were prepared from the polymeric precursors method and the obtained powders were characterized by surface area by the BET method. SnO2 powders with varied MnO2 concentrations were pressed in cylindrical shape, and sintered in a dilatometer furnace with constant heating rate and controlled atmospheres. Sintered samples were characterized by scanning electron microscopy. The influence of atmosphere (argon, air or CO2) as well as of the MnO2 concentrations on the sintering kinetics was determined. The kinetics data of linear shrinkage were analyzed in terms of kinetic models for the initial stage of sintering (Woolfrey and Bannister) as well as for the global sintering (Su e Johnson) allowing the determination of the apparent activation energy. Following the determination of the master sintering curve the apparent activation energy of all sintering process were determined as well as its dependence with the atmosphere and manganese concentrations. Based on these values and on the n exponent, determined by the classical grain growth equation, it was concluded that the most probable sintering mechanism is grain boundary diffusion with surface redistribution controlling the kinetics.